2018
DOI: 10.1093/jas/sky363
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chronic melatonin supplementation during mid to late gestation on maternal uterine artery blood flow and subsequent development of male offspring in beef cattle

Abstract: The objective of the current study was to examine the effects of supplemental melatonin implants on uterine artery blood flow from mid to late gestation in beef cattle and subsequent development of their male offspring. Commercial beef heifers (n = 32) and cows (n = 25) were bred via artificial insemination and assigned to 1 of 2 groups supplemented with melatonin implants (MEL) or without (CON) at day 180, 210, and 240 of gestation. Uterine artery blood flow was determined using color Doppler ultrasonography.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…In agreement with the current results, the ipsilateral uterine arteries BFV of pregnant heifers were higher than their contralateral in heifers (Brockus et al., 2016) and cows (McCarty et al., 2018). Similar to the highest ipsilateral uterine artery blood flow volume (BFV) observed in cyclic cows treated with melatonin on days −4 and 5 of this study, late pregnant heifers treated with melatonin obtained higher ipsilateral uterine artery blood flow by 32% and total uterine blood flow by 27% (Brockus et al., 2016).…”
Section: Discussionsupporting
confidence: 92%
“…In agreement with the current results, the ipsilateral uterine arteries BFV of pregnant heifers were higher than their contralateral in heifers (Brockus et al., 2016) and cows (McCarty et al., 2018). Similar to the highest ipsilateral uterine artery blood flow volume (BFV) observed in cyclic cows treated with melatonin on days −4 and 5 of this study, late pregnant heifers treated with melatonin obtained higher ipsilateral uterine artery blood flow by 32% and total uterine blood flow by 27% (Brockus et al., 2016).…”
Section: Discussionsupporting
confidence: 92%
“…It has also been observed that in this type of cow the age at which animals undergo the functional selection process called "tenta" is a fundamental information to understand the later age of the animal to reach the first calving. The functional test of selection of future breeders of "Brava dos Açores" in the Azores is performed when heifers are between 18 and 26 months, being in the case of approved, placed in the group of breeding cows [19]. Another important fact is that the age at first calving of the heifers in the Iberian Peninsula is influenced by the geographic area and climatological characteristics of the cows, being related to the expected in a breed essentially produced in an extensive way [20].…”
Section: Resultsmentioning
confidence: 99%
“…In the present study it was observed that the mean value of the interval between births is 680 ± 75 days and that 75% of the cows presented a mean interval between calving of 730 ± 37days. These animals are known are more adapted animals, more rustic and with much less human care [19]. In herds of beef cattle such as "brava dos…”
Section: Resultsmentioning
confidence: 99%
“…Slides were then rinsed three times with TBS 1% for 10 min each and incubated with secondary antibody, Goat Anti-Rabbit IgG H&L (Alexa Fluor 594; ab150080; Abcam, Cambridge, MA, USA) for 1 h. Next, slides were rinsed three times with TBS 1% for 10 min each and rinsed with tap distilled water for 2 min. Lastly, slides were counterstained with 1–2 drops of Fluoroshield mounting medium with DAPI (ab104139; Abcam, Cambridge, MA) for nuclear staining [ 22 , 23 ]. Cell wall was identified in histological sections using Wheat Germ Agglutinin Alexa Fluor 488 (Invitrogen, Walthan, MA, USA) [ 7 ].…”
Section: Methodsmentioning
confidence: 99%